2016
DOI: 10.2306/scienceasia1513-1874.2016.42.012
|View full text |Cite
|
Sign up to set email alerts
|

Citrus hystrix (makrut oil) oral sprays inhibit Streptococcus mutans biofilm formation

Abstract: This study evaluated the susceptibility of Streptococcus mutans (ATCC 25175) and 9 clinical isolates from Thai children to different formulations of Citrus hystrix essential oils. All strains were incubated for 3 and 6 h to form biofilms suitable for susceptibility tests. This study also evaluated the inhibitory effect of each oil formulation on growth and biofilm formation of S. mutans (ATCC 25175) using a 96-well polystyrene plate biofilm assay, and analysed the selected formulations that showed the most inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Limonene was found as an inhibitor of streptococcal biofilm formation in subrameniam study (20). In addition, Mitrakul reported that Citrus EOs contain L-limonene inhibited streptococcus mutants biofilm formation (21). Antimicrobial effects of the EOs of Myrtus against several bacterial and fungal strains such as Staphylococcus aureus and Streptococcus pneumonia were also reported by Baharvand-Ahmadi et al (22).…”
Section: Introductionmentioning
confidence: 63%
“…Limonene was found as an inhibitor of streptococcal biofilm formation in subrameniam study (20). In addition, Mitrakul reported that Citrus EOs contain L-limonene inhibited streptococcus mutants biofilm formation (21). Antimicrobial effects of the EOs of Myrtus against several bacterial and fungal strains such as Staphylococcus aureus and Streptococcus pneumonia were also reported by Baharvand-Ahmadi et al (22).…”
Section: Introductionmentioning
confidence: 63%